Economic Impact Analysis of a Mega Project on Petroleum Refinery: A Case Study of the Proposed Ratnagiri Refinery in Maharashtra. (August 2022) - Bandyopadhyay, Saurabh; Biswas, Pradip Kumar; Pratap, Devender; Joshi, Laxmi; Sahu, Ajaya K.
An economic evaluation of mega projects is very important for taking into account important aspects connected with investment and operation costs, their possible overflows and the fulfilment of the time period intended for the project. But it is also needed for monitoring the impact of the projects on the overall economy and the regional surroundings. The main objective of the present article is the evaluation of a particular mega project, that is, Ratnagiri Refinery and Petrochemicals Limited, by examining the various aspects of economic evaluation using a new methodology for the estimation of the specific impact in the project evaluation. JEL Codes: C67, L71, L74